2007
DOI: 10.1097/01.mpg.0000252196.91707.ff
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Capsule Endoscopy in Children: A Study to Assess Diagnostic Yield in Small Bowel Disease in Paediatric Patients

Abstract: WCE led to a positive alteration in management in 18/24 (75%) of patients whose small bowel was examined by WCE and in 18/28 (64.3%) who were admitted to the study. WCE was safe, well tolerated, and more sensitive than radiological and standard endoscopic modalities in the detection of small bowel CD distribution, GIB source, and presence of polyps in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 36 publications
3
80
0
3
Order By: Relevance
“…Most SBCE studies included patients who had negative colonoscopies and SBFT [108,117]. Thomson et al [114] showed that SBCE is more sensitive for small-bowel pathology than SBFT (out of 19 children who had abnormalities on SBCE, only 5 had abnormal results at SBFT) and than upper intestinal endoscopy with ileocolonoscopy (only 10 had endoscopic findings compared with 23 at SBCE). Data from paediatric case series suggests that SBCE is superior to SBFT/SBE for detecting small-bowel pathology.…”
Section: How Does Sbce Compare With Other Imaging Modalities In Paedimentioning
confidence: 99%
“…Most SBCE studies included patients who had negative colonoscopies and SBFT [108,117]. Thomson et al [114] showed that SBCE is more sensitive for small-bowel pathology than SBFT (out of 19 children who had abnormalities on SBCE, only 5 had abnormal results at SBFT) and than upper intestinal endoscopy with ileocolonoscopy (only 10 had endoscopic findings compared with 23 at SBCE). Data from paediatric case series suggests that SBCE is superior to SBFT/SBE for detecting small-bowel pathology.…”
Section: How Does Sbce Compare With Other Imaging Modalities In Paedimentioning
confidence: 99%
“…The technique is approved by the FDA for use in children ≥2 years of age 34 and safe use has been demonstrated in infants as young as 10 months 35 . Capsules are inherently less invasive than standard endoscopes as they move through the body via natural motion induced by peristalsis rather than being manually manoeuvred by the clinician.…”
Section: Biomarkers For Eedmentioning
confidence: 99%
“…Because a known CD increases a risk of capsule retention possibly caused by an intestinal stricture (Cheifetz, 2006;Moy, 2009;Atay, 2009), it is recommended to avoid the use of CE for the evaluation of known CD in both adult and children. In regard to the diagnostic accuracy, the previous pediatric study elucidated that CE was a more effective diagnostic tool in established CD patients compared with small-bowel radiography, CTE, and push enteroscopy (Thomson, 2007). Further, CE provides evidence not only to diagnose a patient having CD but also exclude CD and discriminate CD from indeterminate colitis.…”
Section: Chron's Disease or Inflammatory Bowel Diseasementioning
confidence: 99%
“…Another pediatric study described that 6/12 patients with abdominal pain had abnormal findings in which 3 with small bowel CD, 2 lymph nodular hyperplasia, and 1 blue rubber bleb syndrome, however it is undescribed whether those patients had additional symptoms or signs (Fritscher-Ravens, 2009). CE evaluation for a patient with recurrent abdominal pain reported a self-resolving ileojejunal intussusceptions in the mid-small bowel (Thomson, 2007). Taken together, as well as adult patients, it is indicated that CE doesn't provide diagnostic value against abdominal pain in children, but additional symptoms or signs may increase the demand of CE.…”
Section: Abdominal Painmentioning
confidence: 99%
See 1 more Smart Citation